CircNR3C1 inhibits proliferation of bladder cancer cells by sponging miR-27a-3p and downregulating cyclin D1 expression. (28th September 2019) - Zheng, Fuxin; Wang, Miao; Li, Yawei; Huang, Chao; Tao, Dan; Xie, Fei; Zhang, Hui; Sun, Jiayin; Zhang, Chuanhua; Gu, Chaohui; Wang, Zhendi; Jiang, Guosong
Abstract: Accumulating evidences suggest that circular RNAs play vital roles in human cancers. Previously, we found that circHIPK3 suppressed invasion of bladder cancer cells via sponging miR-558 and downregulating heparanase expression. In this study, we discovered that a circular RNA derived from NR3C1 (circNR3C1) was downregulated in bladder cancer tissues and cell lines according to RNA-Seq data and qRT-PCR analysis. Functionally, we found that overexpression of circNR3C1 could significantly inhibit cell cycle progression and proliferation of bladder cancer cells in vitro, as well as suppress tumor growth in vivo. Mechanistically, we demonstrated that circNR3C1 possessed four targeting sites of miR-27a-3p and could effectively sponge miR-27a-3p to suppress the expression of cyclin D1. Furthermore, we revealed that miR-27a-3p functioned as an oncogene through interacting with 5′UTR of cyclin D1 to enhance its expression, which led to promote cell cycle progression and proliferation in bladder cancer cells. Conclusively, our findings further confirm the hypothesis that circRNAs function as "microRNA sponges", and our data suggest that circNR3C1 and miR-27a-3p would be potential therapeutic targets for bladder cancer treatment. Highlights: CircNR3C1 is down-regulated in bladder cancer. CircNR3C1 could inhibit cell cycle and cell proliferation in bladder cancer cells. CircNR3C1 could directly sponge miR-27a-3p in bladder cancer. miR-27a-3p could promote cell proliferation and cycle progression. miR-27a-3p could interact with cyclinD1 5′UTR to enhance cyclinD1 expression.